Melittin and diclofenac synergistically promote wound healing in a pathway involving TGF-β1. (January 2022) - Eid, Basma G.; Alhakamy, Nabil A.; Fahmy, Usama A.; Ahmed, Osama A.A.; Md, Shadab; Abdel-Naim, Ashraf B.; Caruso, Giuseppe; Caraci, Filippo
Abstract: A dysregulation of the wound healing process can lead to the development of various intractable ulcers or excessive scar formation. Therefore it is essential to identify novel pharmacological strategies to promote wound healing and restore the mechanical integrity of injured tissue. The goal of the present study was to formulate a nano-complex containing melittin (MEL) and diclofenac (DCL) with the aim to evaluate their synergism and preclinical efficacy in an in vivo model of acute wound. After its preparation and characterization, the therapeutic potential of the combined nano-complexes was evaluated. MEL-DCL nano-complexes exhibited better regenerated epithelium, keratinization, epidermal proliferation, and granulation tissue formation, which in turn showed better wound healing activity compared to MEL, DCL, or positive control. The nano-complexes also showed significantly enhanced antioxidant activity. Treatment of wounded skin with MEL-DCL nano-complexes showed significant reduction of interleukin-6 (IL-6), IL-1β, and tumor necrosis factor-α (TNF-α) pro-inflammatory markers that was paralleled by a substantial increase in mRNA expression levels of collagen, type I, alpha 1 ( Col1A1 ) and collagen, type IV, alpha 1 ( Col4A1 ), and hydroxyproline content as compared to individual drugs. Additionally, MEL-DCL nano-complexes were able to significantly increase hypoxia-inducible factor 1-alpha (HIF-1α) and transforming growth factor beta 1 (TGF-β1) proteins expression compared to single drugs or negative control group. SB431542, a selective inhibitor of type-1 TGF-β receptor, significantly prevented in our in vitro assay the wound healing process induced by the MEL-DCL nano-complexes, suggesting a key role of TGF-β1 in the wound closure. In conclusion, the nano-complex of MEL-DCL represents a novel pharmacological tool that can be topically applied to improve wound healing. Graphical Abstract: ga1